Fithrah: Kajian Personal Grooming - Zikriadi; Aisyah Arsyad; Ghalib (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research discusses the nature of self-appearance or (personal grooming) which includes the obligation to maintain cleanliness, both physically and mentally. This nature is attached to the individual. This research is included in the literature review, the object of this study is the verses of the Koran and epistemology related to the nature of personal grooming, the approach used is the thematic interpretation related to nature in the perspective of a literature review related to nature and cleanliness. The results of the study reveal that self-appearance is part of aesthetics in Islam or enters into the context of adab or ethics, as part of human nature. For this reason, self-appearance (personal grooming) is also part of the form of self-cleaning, as a manifestation of good luck.